Pertumbuhan dan Produksi Tanaman Kacang hijau (Vigna radiata L.) Akibat Pemberian Kompos Kubis dan Pupuk Organik Cair Urine Kambing - Armaniar, Armaniar; Br.Sitepu, Sri Mahareni; Pranata, Rizky Ferdi (UNIVERSITAS LABUHANBATU, 2024)
The aim of this research was to determine the response of growth and production of green bean plants (Vigna radiata L.) to the application of cabbage compost and goat urine liquid organic fertilizer. This research method used a factorial Randomized Block Design (RBD), consisting of 16 treatments and 3 replications so there were 48 experiments. The treatments studied were: giving cabbage compost with the symbol